An Overview of Self-Control in Juvenile Delinquents Index Offenses in Makassar City - As'ad, Febriani Saidar; Firdaus, Faradillah; ., Irdianti (Polteknik Ilmu Pemasyarakatan, 2024)
Juvenile delinquency is a problem that often occurs in the social environment. Adolescents' ability to control themselves from various deviant behaviors is an important component in reducing and avoiding various destructive actions. This research aims to determine the description of self-control among juvenile delinquency index offenders in Makassar City. The research uses a qualitative approach with a case study method. This research involved 6 respondents who were criminals who were in conflict with the law in Makassar City. Data collection was carried out through direct observation and interviews with subjects. Interviews were carried out repeatedly on each subject to deepen information and perfect the research data, observations were carried out directly on each subject during the research process. Data analysis techniques are carried out through thematic analysis to identify general patterns, variations and similarities that arise in research subjects in order to understand hidden meanings in the data studied. The research results show that there is a role of self-control in juvenile delinquency index offenses in Makassar City. The research data shows that there is a different role in the aspect of self-control in deviant behavior committed by each juvenile delinquent subject. It is hoped that this research will be able to provide relevant information about self-control among juvenile offenders with index offenses and increase public awareness, especially teenagers, regarding self-control and destructive behavior that is detrimental in the social environment.